2005
DOI: 10.1111/j.1742-1241.2005.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a structured migraine diary improves patient and physician communication about migraine disability and treatment outcomes

Abstract: Migraine is frequently undertreated, perhaps because impaired communication between patients and physicians underestimate the disability associated with migraine attacks. The purpose of this study was to evaluate the benefits of a structured migraine diary used during a prospective open-label study of triptan-naive patients in Spain for recording information on response to therapy for a pre-study migraine attack and three consecutive migraine attacks, the first and third treated with rizatriptan 10-mg wafer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…The first is through standardizing methods of gaining information regarding headache. Utilization of surveys about headache symptoms and quality of life (such as the Migraine Disability Assessment or MIDAS), 123 and standard headache diaries, 124 can provide a starting point for conversations about migraine symptoms and improve communication about migraine. 124,125 The second method is through improving communication techniques to enhance understanding between the physician and patient.…”
Section: Patientàphysician Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is through standardizing methods of gaining information regarding headache. Utilization of surveys about headache symptoms and quality of life (such as the Migraine Disability Assessment or MIDAS), 123 and standard headache diaries, 124 can provide a starting point for conversations about migraine symptoms and improve communication about migraine. 124,125 The second method is through improving communication techniques to enhance understanding between the physician and patient.…”
Section: Patientàphysician Communicationmentioning
confidence: 99%
“…Utilization of surveys about headache symptoms and quality of life (such as the Migraine Disability Assessment or MIDAS), 123 and standard headache diaries, 124 can provide a starting point for conversations about migraine symptoms and improve communication about migraine. 124,125 The second method is through improving communication techniques to enhance understanding between the physician and patient. 126 One useful technique is the "askÀtellÀask" method of communication, which involves asking an open-ended question, relaying in simple terms information pertinent to the patient's treatment, and then, to ensure understanding, requesting that the patient rephrase what was just communicated.…”
Section: Patientàphysician Communicationmentioning
confidence: 99%
“…Tracking can be an effective part of managing chronic illness, improving health outcomes [18] as well as communication with healthcare providers [19]. The Pew Internet & American Life Project [10] recently reported that 69% of Americans track health data for themselves or a loved one.…”
Section: Self-trackingmentioning
confidence: 99%
“…Pain diaries help patients to better assess their pain [de Wit et al 1999] and even reduce it [Cruise et al 1996]. They also improve communication between physicians and patients [Baos et al 2005]. Non-compliance with medical regimens prescribed by physicians is a major problem in chronic disease care [Cochrane et al 1999;Vermeire et al 2001] and patient diaries were shown to improve it [van Berge Henegouwen et al 1999].…”
Section: Introductionmentioning
confidence: 99%